Metastatic nasopharyngeal carcinoma: Patterns of care and survival for patients receiving chemotherapy with and without local radiotherapy. Issue 1 (July 2017) - Rusthoven, Chad G.; Lanning, Ryan M.; Jones, Bernard L.; Amini, Arya; Koshy, Matthew; Sher, David J.; Bowles, Daniel W.; McDermott, Jessica D.; Jimeno, Antonio; Karam, Sana D.
Abstract: Background and purpose: Radiotherapy (RT) to the primary nasopharyngeal tumor is frequently offered to patients with metastatic nasopharyngeal carcinoma (mNPC). However, only limited data exist to support RT in this setting. We used the National Cancer Database (NCDB) to evaluate outcomes for mNPC patients receiving chemotherapy with and without local RT. Methods: The NCDB was queried for patients with mNPC with synchronous metastatic disease at diagnosis who received chemotherapy. Overall survival (OS) was analyzed using the Kaplan–Meier method, Cox proportional hazards models, and propensity score-matched analyses. Results: From 2004 to 2013, 718 cases were identified (39% chemotherapy-alone, 61% chemotherapy + RT). At a median follow-up of 4.4 years, RT was associated with improved survival on univariate analysis (median OS 21.4 vs 15.5 months; 5-year OS 28% vs 10%; p < 0.001) and multivariate analyses (HR, 0.61; CI, 0.51–0.74; p < 0.001). Propensity score analysis with matched baseline characteristics demonstrated a similar OS advantage with RT (HR, 0.68; CI, 0.55–0.84; p < 0.001). The benefits of RT remained consistent in models controlling for single vs multi-organ metastases and anatomic sites of metastatic involvement. RT dose was an independent prognostic factor as both a continuous and categorical variable, with OS benefits observed among patients receiving ≥50 Gy. Long-term survival of >10 years was only observed in the RT cohort. Conclusions: This analysis supports strategies incorporating local RT with chemotherapy for mNPC. Prospective trials evaluating RT integration for mNPC are warranted.